Ultrabroadband Electro-Optic Modulator Based on Hybrid Silicon-Polymer Dual Vertical Slot Waveguide. (11th August 2010) - Shi, Shouyuan; Prather, Dennis W.
Abstract : We present a novel hybrid silicon-polymer dual slot waveguide for high speed and ultra-low driving voltage electro-optic (EO) modulation. The proposed design utilizes the unique properties of ferroelectric materials such as LiNbO3 to achieve dual RF and optical modes within a low index nanoslot. The tight mode concentration and overlap in the slot allow the infiltrated organic EO polymers to experience enhanced nonlinear interaction with the applied electric field. Half-wavelength voltage-length product and electro-optic response are rigorously simulated to characterize the proposed design, which reveals ultrabroadband operation, up to 250 GHz, and subvolt driving voltage for a 1 cm long modulator.